Temperature versus resource constraints: which factors determine bee diversity on Mount Kilimanjaro, Tanzania?. Issue 6 (19th January 2015) - Classen, Alice; Peters, Marcell K.; Kindeketa, William J.; Appelhans, Tim; Eardley, Connal D.; Gikungu, Mary W.; Hemp, Andreas; Nauss, Thomas; Steffan‐Dewenter, Ingolf
Abstract Aim Understanding the mechanisms controlling variation in species richness along environmental gradients is one of the most important objectives in ecology. Resource availability is often considered as the major driver of animal diversity. However, in ectotherms, temperature might play a predominant role as it modulates metabolic rates and the access of animals to resources. Here, we investigate the relative importance of resource availability and temperature in determining the diversity pattern of bees along a 3.6‐km elevational gradient. Location Mount Kilimanjaro, Tanzania. Methods We assessed bee species richness and abundance with pan traps and floral resources with transect records on 60 study sites which were equally distributed over six near‐natural and six disturbed habitat types along an elevational gradient from 870 to 4550 m a.s.l. We used path analysis to disentangle the effects of temperature, precipitation, floral resource abundance, bee abundance and land use on bee species richness. In addition, we monitored flower visitation rates during transect walks at different elevations to evaluate the temperature dependence of bee–flower interactions. Results Bee species richness continuously declined with elevation in natural and disturbed habitats. While the abundance of floral resources had a significant but only weak effect on species richness, the effect of temperature was strong. Temperature had a strong positive effect on species richness that was not mediated by bee abundance and an indirect effect via bee abundances. We observed higher levels of bee–flower interactions at higher temperatures, supporting the hypothesis that temperature limits diversity by constraining resource exploitation in ectotherms. Main conclusions Temperature and the availability of resources shape species richness patterns along environmental gradients. In ectothermic organisms like bees temperature seems to have the more important role, as it both limits the access to resources (abundance‐mediated effect) and accelerates other (abundance‐independent) ecological and evolutionary processes that drive the maintenance and origination of diversity.